The economic costs of a multisectoral nutrition programme implemented through a credit platform in Bangladesh. Issue 1 (18th October 2022) - Thai, Giang; Margolies, Amy; Gelli, Aulo; Sultana, Nasrin; Choo, Esther; Kumar, Neha; Levin, Carol
Abstract: Bangladesh struggles with undernutrition in women and young children. Nutrition‐sensitive agriculture programmes can help address rural undernutrition. However, questions remain on the costs of multisectoral programmes. This study estimates the economic costs of the Targeting and Re‐aligning Agriculture to Improve Nutrition (TRAIN) programme, which integrated nutrition behaviour change and agricultural extension with a credit platform to support women's income generation. We used the Strengthening Economic Evaluation for Multisectoral Strategies for Nutrition (SEEMS‐Nutrition) approach. The approach aligns costs with a multisectoral nutrition typology, identifying inputs and costs along programme impact pathways. We measure and allocate costs for activities and inputs, combining expenditures and micro‐costing. Quantitative and qualitative data were collected retrospectively from implementers and beneficiaries. Expenditure data and economic costs were combined to calculate incremental economic costs. The intervention was designed around a randomised control trial. Incremental costs are presented by treatment arm. The total incremental cost was 795, 040.34 for a 3.5‐year period. The annual incremental costs per household were US65.37 (Arm 2), USD114.15 (Arm 3) and 157.11 (Arm 4). Total costs were led by nutrition counselling (37%), agriculture extension (12%), supervision (12%), training (12%), monitoring and evaluation (9%) and community events (5%). Total input costs were led by personnel (68%), travel (12%) and supplies (7%). This study presents the total incremental costs of an agriculture‐nutrition intervention implemented through a microcredit platform. Costs per household compare favourably with similar interventions. Our results illustrate the value of a standardised costing approach for comparison with other multisectoral nutrition interventions. Abstract : Key messages: Nutrition‐sensitive agriculture programmes can improve rural undernutrition but lack information on costs. We use a standardised approach to estimate the total incremental costs of an integrated nutrition intervention in Bangladesh to improve maternal and child undernutrition. Costs per household compare favourably with similar interventions. This study provides evidence on the costs of integration to support the design and implementation of multisectoral nutrition programmes. Our results illustrate the value of standardising costing to facilitate comparisons with other multisectoral nutrition interventions.